In the Shadow of Post-Modernism - Sedová, Tatiana (Organon F, 1994)
In this paper the author developes an account of the issues of post-modernism. This account is then used to discuss the difference between the concept of philosophy as knowledge or as "Weltanschauung". The author offers a critique of the post-modern philosophy and argues that, post-modernism does not distinguish epistemology from social ethics topics. All topisc are considered in relation to the situation of philosophy in Slovakia.